Interests and integration : market liberalization, public opinion, and European Union / Matthew J. Gabel. - Gabel, Matthew J. (University of Michigan Press, 1998)
Integration in Europe has been a slow incremental process focusing largely on economic matters. Policymakers have tried to develop greater support for the European Union by such steps as creating pan-European political institutions - and yet significant opposition remains to policies such as the creation of a single currency.